The Effect of Competency and Workload on Services at Solok District Community Health Center with Organizational Citizenship Behavior (OCB) as an Intervening Variable - Barmitoni Barmitoni; Lusiana Lusiana; Vicky Brama Kumbara (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the influence of competence and workload on services at Solok Regency Community Health Centers (Puskesmas), with organizational citizenship behavior (OCB) as an intervening variable. Data collection methods included a survey and questionnaire distribution, with a sample of 90 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant influence of competence on organizational citizenship behavior (OCB) at Solok Regency Community Health Centers. There was a significant influence of workload on organizational citizenship behavior (OCB) at Solok Regency Community Health Centers. There was a significant influence of competence on services at Solok Regency Community Health Centers. There was a significant influence of workload on services at Solok Regency Community Health Centers. There was a significant influence of organizational citizenship behavior (OCB) on services at Solok Regency Community Health Centers. Organizational citizenship behavior (OCB) mediated the influence of competence on services at Solok Regency Community Health Centers. Organizational citizenship behavior (OCB) mediated the influence of workload on services at Solok Regency Community Health Centers.